Pengaruh Kandungan Ekstrak Daun Zodia (Evodia suaveolens) Terhadap Mortalitas Larva Nyamuk Aedes aegypti - Basundari, Sinta Anas; Tarwotjo, Udi; Kusdiyantini, Endang (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
Aedes aegypti mosquito is a vector of dengue hemorrhagic fever (DHF). One place that is endemic by A.aegypti mosquitoes is the city of Semarang, specificallyÂ in Tembalang District. Tembalang district is one of the areas with highest DHF incidence rate. A.aegypti mosquito vector control is still using artificial insecticide, where the insecticide has negative impact to health and environment. Zodia leaves (Evodia suaveolens) are known to have potential as a natural insecticide, because they have secondary metabolites such as tannins, alkaloids, flavonoids that can be used as biolarvasides. This study aims to determine the content of phytochemical compounds of zodia leaves extract and to know the mortality in each population to zodia leaves extract. The extract of zodia leaf is obtained using maceration method. Chemical compounds contained in zodia leaves were analyzed using FT-IR. This research method is bioassay test, where the larvae are soaked with various series of concentration of zodia leaf extract. Each series of concentrations required ten larvae. The larvae used came from five kelurahan in Tembalang Subdistrict. The data were processed using probit analysis to obtain LC50. The results of LC50 obtained from the smallest to largest is 39,94 (34,67-45,28); 41,98 (36,6-48,07); 46,18 (39,28- 53,97); 47,62 (39,92-54,32) and 49,44 (42,24-58,25). The result of LC50 shows that is not significantly different, because there is the value of the overlapping fiducial limits between each population